Temi misogini al servizio del saber: il caso del «Sendebar» castigliano (Carte Romanze, 2020)
The paper analyzes the misogynistic stories of Sendebar, showing how they relate in a deep and systematic way with the main theme of the collection, the search and construction of perfect wisdom.
Keywords: Sendebar; misogyny; wisdom